The Uses of remote sensing and GIS in deriving surface water maps in the Sirwan River basin in the Kurdistan Region of Iraq - Tahseen Azeez (Zanco Journal of Humanity Sciences)
This study aims to derive surface water maps in the Sirwan River Basin (Darbandikhan Lake Basin) in the Kurdistan Region of Iraq through remote sensing data and geographic information systems programs, and to determine the areas covered by water at different times, which is one of the modern methods to know the reality of surface water resources.